Identification of Vine Weeds in Florida Citrus - Stephen H. Futch; David W. Hall (EDIS)
Vines are classified as broadleaf plants. As with other plants, they are classified as either annuals, biennials, or perennials. A combination of leaf, stem, fruit, and/or seed characteristics will aid in the identification process. A useful guide of characteristics to identify broadleaf plants are included at the end of this article. This document is HS926, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published August 2003.